Faktor-Faktor Yang Mempengaruhi Mahasiswa Akuntansi Terhadap Pemilihan Karir Sebagai Konsultan Pajak - Lorenia Pranata; Poniman Poniman (eCo-Buss, 2024)
A tax consultant's profession requires individuals who possess a strong work ethic, are willing to take on risks, have a capacity for acquiring new knowledge, and, most importantly, can comprehend and apply tax regulations. The selection of an individual's profession is a protracted and multifaceted process. Perception, professional recognition, and self-efficacy are influential factors in individuals' job decision-making. This study employs a quantitative approach, utilizing the Slovin algorithm to choose a sample of 93 respondents. The findings indicated that the perception variable had a notable impact on the selection of a career as a tax consultant, with a t count of 4.712, which exceeded the critical value of 1.987 from the t table. Professional recognition has a substantial impact on the career choice of a tax consultant, as evidenced by a t count of 3.216, which is greater than the t table value of 1.987. Self-efficacy strongly influences the decision to pursue a career as a tax consultant, as evidenced by a t count of 2,348, which exceeds the critical value of 1,987 from the t table. The variables of perception, professional recognition, and self-efficacy all have a simultaneous and considerable impact on the career choice of becoming a tax consultant. This is evidenced by the F statistic of 64.549, which is larger than the critical F value of 3.09, and a significant p-value of 0.000, which is less than the threshold of 0.05.